Jaguar e ideología en las sociedades del Período Formativo: Pacopampa un caso en los Andes centrales - Morales Chocano, Daniel (2007)
In the Peruvian Central Andean Range the material culture of societies of the Formative Period (1500 to 400 B.C.) include anthropomorphic jaguars in their iconography. Archaeological diggings in the Pacopampa site have unearthed the iconographic representation of anthropomorphic jaguars as recurrent elements in pottery with incisions. This character would be linked to the idea of the Jaguar God, that in our opinion, represents the supernatural powers that control natural phenomena during the various seasons. The jaguar icons in Pacopampa evolve from the animal natural figure and become anthropomorphic figures in a process that based on ethnographic data is interpreted as the transformation of shaman into jaguar, its most eloquent image in the Andean world being the Raimondi Stele of Chavin. According to Julio C. Tello this image continued to evolve to become the Wiracocha god of the Incas.